A new 4‐D hyperchaotic two‐scroll system with hidden attractor and its field‐programmable gate array implementation - Vaidyanathan, Sundarapandian; Benkouider, Khaled; Ovilla‐Martinez, Brisbane; Tlelo‐Cuautle, Esteban; Sambas, Aceng; Darwin, P. (International journal of circuit theory and applications, 2023)
This research work reports the finding of a new 4‐D hyperchaotic two‐scroll system having three second‐order nonlinear terms. It is detailed that the system does not have any rest point for non‐zero values of the system parameters. Thus, we deduce that the new hyperchaotic system has a hidden attractor. The main findings of the new hyperchaotic system include a detailed bifurcation analysis, coexisting attractors, and offset‐boosting control. The new 4‐D hyperchaotic two‐scroll system with hidden attractor is prototyped using the field‐programmable gate array (FPGA) Zybo Z7‐20 development board, Xilinx Vivado tool, and the hardware description by VHDL. It is highlighted that the simulation of the circuit design, and the experimental results from the FPGA synthesis, all of them are in good agreement with theoretical simulations.